2009
DOI: 10.1124/jpet.109.159517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tumor Necrosis Factor-Related Apoptosis-Inducing Ligand on the Reduction of Joint Inflammation in Experimental Rheumatoid Arthritis

Abstract: This study focused on the potential therapeutic effect of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) on collagen-induced arthritis (CIA) and on the elucidation of the mechanisms involved. DBA/1J mice with established CIA were treated with various amount of recombinant soluble human TRAIL. The effects of TRAIL on the development and severity of CIA in this DBA/1J mouse model were assessed clinically and histologically, and a detailed investigation was conducted on proinflammatory cytokine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 36 publications
4
23
0
1
Order By: Relevance
“…Recent reports indicate that treatment with the pro-apoptotic death ligand TRAIL ameliorates disease activity in animal models of RA [27][28][29]. In another study, TRAIL appeared to inhibit DNA synthesis and cell cycle progression in inflammatory cells, but lacked direct apoptotic activity [46].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recent reports indicate that treatment with the pro-apoptotic death ligand TRAIL ameliorates disease activity in animal models of RA [27][28][29]. In another study, TRAIL appeared to inhibit DNA synthesis and cell cycle progression in inflammatory cells, but lacked direct apoptotic activity [46].…”
Section: Discussionmentioning
confidence: 95%
“…Taken together, these data indicate that the various T H1 subpopulations analyzed are susceptible to treatment with scFvCD7:sFasL, whereas T H2 cell types are largely resistant. (sTRAIL) [27][28][29]. Therefore, we performed a side-by-side comparison of the apoptotic activity of fusion protein scFvCD7:sFasL and scFvCD7:sTRAIL.…”
Section: Scfvcd7:sfasl Potently Activates Apoptosis In Various Subsetmentioning
confidence: 99%
“…This septic sera factor was not identified but our data suggest elevated plasma TRAIL can increase T cell apoptosis when TSP-1 is concomitantly present. Since TRAIL alone is unable to mediate apoptosis in primary stimulated T cells, an additional serum mediator needs to be involved in mediating the control T cell apoptosis induced by trauma patients’ sera [13, 27, 28]. TSP-1 is increased post-injury and can trigger CD47 (its receptor) on T cells to induce apoptosis [15, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Jin et al. reported that TRAIL‐expressing B cells can inhibit cellular immune responses and inflammatory cell infiltration with reduced proinflammatory cytokine and Ab production in collagen‐induced arthritis mice . Upon engagement with TRAIL receptors on target cells, TRAIL expressed by B cells activates apoptosis inducing signaling cascades, ultimately leading to cell death …”
Section: Immunoregulatory Network Of Bregsmentioning
confidence: 99%